The Utilization of Traditional Conservation of Sumatran Tiger as a Potential Development of Biology Teaching Materials - Ovi Zurah Mei; I Gusti Putu Suryadarma (Pascasarjana, Mataram University, 2023)
Indigenous communities have long had an unwritten norm system that regulates the protection of forests and biodiversity inside. The principle of traditional conservation on the island of Sumatra for the preservation of Sumatran tigers is to implement environmental management in the form of prohibitions or invitations in forest areas. On the other hand, this cultural concept is intertwined with learning. Students can discuss lesson concepts in a cultural perspective to support meaningful learning in biology lessons. Therefore, the purpose of this study is to find out the values of traditional conservation of the Sumatran tiger which can be used as a source of developing biology teaching materials based on cultural perspective. The method used in this research is a literature review and content analysis. Researchers searched works of literature from multiple data search engines, namely PubMed, Google Scholar, Mendeley, Semantic Scholar and the Publish or Perish. Data is processed and analyzed according to research needs. Based on the results of the study, obtained results regarding the identification of Sumatran tiger, threats, and forms of conservation in the natural habitat of the Sumatran tiger. Based on the Curriculum 2013, the relevance of this study is linked to the biology material on biodiversity in basic competencies 3.2 and 4.2 regarding distribution, threat analysis, and conservation efforts of biodiversity for the grade of 10-th of high school. The material is also included in the learning outcomes of the Merdeka Curriculum phase E for class x regarding understanding and process skills analyzing interactions between ecosystem components and efforts to conserve biodiversity. These material resources can be developed into a module-based on local culture to be studied independently by students.